An Interventional Radiology Odyssey The Story of My Life and Work - Rösch, Josef (Springer Biographies, 2016)
In this autobiography, Josef Rösch, a leading pioneer in interventional radiology from its inception to the present, documents his life and discusses important aspects of his work, focusing especially on those procedures that he developed or improved and that were popularized by his lectures and publications. In Prague, Dr. Rösch worked on splenoportography and visceral angiography, while in the United States he developed the transjugular intrahepatic portosystemic shunt (TIPS) and introduced embolization for treatment of GI bleeding and expandable metallic stenting of obstructions of major veins and the esophagus. In addition, he contributed to the improvement of coronary angiography and fallopian tube catheterization. The book also describes the author's role as the lead person in establishing the Dotter Interventional Institute in 1990. The Institute was the first freestanding, independent interventional radiology unit to deal with education, research, and patient care. Dr. Rösch's organization of scientific meetings and his early use of techniques for live internet broadcasting are described, and the book concludes by summarizing the multiple honors and awards that he received in recognition of his achievements.